Post-marketing safety concerns with lumateperone: a pharmacovigilance analysis based on the FDA adverse event reporting system (FAERS) database - Zhao, Dan; Zhang, Wangxin; Liu, Yan; Yan, Zhaojun (Frontiers in Pharmacology, 2024)
Objective Lumateperone, a novel antipsychotic drug that was granted by the Food and Drug Administration (FDA) approval in December 2019, remains insufficiently explored for its adverse event profile. This study used the FDA Adverse Event Reporting System (FAERS) database to explore its potential safety issues. Methods This study conducted a retrospective analysis of FAERS data from the fourth quarter of 2019 to the third quarter of 2023, extracting reports related to lumateperone. Disproportionality analysis using Reporting Odds Ratio (ROR) and Bayesian Confidence Propagation Neural Network (BCPNN) algorithms was employed to detect signals of adverse events (AEs). Results Our research processed 4,777 pertinent AE disclosures related to lumateperone, unveiling 125 signals that satisfied both ROR and BCPNN evaluative benchmarks across 26 System Organ Classes (SOCs). Intriguingly, 108 of these signals were categorized as unanticipated, spotlighting notable psychiatric manifestations such as mania (ROR = 73.82, 95% CI = 57.09–95.46; IC = 6.16, IC025 = 4.49), and hypomania (ROR = 34.74, 95% CI = 15.54–77.64; IC = 5.10, IC025 = 3.43), alongside non-psychiatric phenomena like urinary retention (ROR = 3.59, 95% CI = 1.80–7.19; IC = 1.84, IC025 = 0.18) and serotonin syndrome (ROR = 8.69, 95% CI = 4.81–15.72; IC = 3.11, IC025 = 1.45). Conclusion This research provides real-world safety data on lumateperone post-marketing and is an important supplement to the information from clinical trial studies. Healthcare professionals should be vigilant for the risk of a manic switch in patients with bipolar depression who are administered lumateperone. More epidemiological studies are needed in the future to explore and further evaluate the risk-benefit issue of lumateperone.